1997
DOI: 10.1590/s0100-879x1997000300014
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipid antigens from Leishmania (L.) amazonensis amastigotes: Binding of anti-glycosphingolipid monoclonal antibodies in vitro and in vivo

Abstract: Specific glycosphingolipid antigens of Leishmania (L.) amazonensis amastigotes reactive with the monoclonal antibodies (MoAbs) ST-3, ST-4 and ST-5 were isolated, and their structure was partially elucidated by negative ion fast atom bombardment mass spectrometry. The glycan moieties of five antigens presented linear sequences of hexoses and N-acetylhexosamines ranging from four to six sugar residues, and the ceramide moieties were found to be composed by a sphingosine d18:1 and fatty acids 24:1 or 16:0. Affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Previous studies on the biological roles of Leishmania glycosphingolipid (GSL) antigens demonstrated that monoclonal antibodies (mAbs) ST-3, ST-4 and ST-5, specifically directed at amastigote L. (L.) amazonensis GSLs, inhibited macrophage invasion by amastigotes by as much as 80%, suggesting that the epitope recognized by these mAbs present in surface GSLs is important in mediating binding of L. (L.) amazonensis amastigotes to macrophages (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the biological roles of Leishmania glycosphingolipid (GSL) antigens demonstrated that monoclonal antibodies (mAbs) ST-3, ST-4 and ST-5, specifically directed at amastigote L. (L.) amazonensis GSLs, inhibited macrophage invasion by amastigotes by as much as 80%, suggesting that the epitope recognized by these mAbs present in surface GSLs is important in mediating binding of L. (L.) amazonensis amastigotes to macrophages (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic differences are known to exist between the promastigote and amastigote stages (11)(12)(13)(14); in addition, several leishmanial molecules have been demonstrated to be up-regulated or specifically associated with the amastigote stage. These include specific glycosphingolipids, parasite lysosomal enzymes (cysteine proteinase(s); arylsulfatase), the Leishmania donovani A2 gene, superoxide dismutase, and the proteophosphoglycan molecule(s) (15)(16)(17)(18)(19). The biological functions of these stage-specific molecules are of interest in terms of their potential role(s) in parasite virulence, pathogenicity, and intracellular survival.…”
mentioning
confidence: 99%
“…Leishmania (Leishmania) amazonensis is responsible for most cases of human cutaneous leishmaniasis in the Amazon region of Brazil.A family of glycosphingolipids (GSLs) was identified in amastigotes of L. (L.) amazonensis (1,18,19). In an earlier report we demonstrated that GSLs purified from L. (L.) amazonensis amastigotes inhibited the proliferation of murine T and B cells (2), suggesting that parasite glycosphingolipids may play a relevant role in leishmaniasis.…”
mentioning
confidence: 99%
“…The neutral GSL fraction purity was analyzed by high-performance thinlayer chromatography using staining with orcinol-H 2 SO 4 and Dittmer-Lester reagent, which detect carbohydrates and phosphodiester linkages, respectively. No contamination with phospholipids or peptides was detected, as described previously (2,18,19). The effect of amastigote GSLs on T-cell responses induced by mitogen was analyzed in lymphocytes purified from human peripheral blood by Ficoll-Hypaque density gradient centrifugation.…”
mentioning
confidence: 99%
See 1 more Smart Citation